Estimation of radiated energy using the KiK-net downhole records—old method for modern data. Issue 2 (23rd January 2020) - Kanamori, Hiroo; Ross, Zachary E; Rivera, Luis
SUMMARY: We use KiK-net (NIED) downhole records to estimate the radiated energy, E R, of 29 Japanese inland earthquakes with a magnitude range from M w  = 5.6 to 7.0. The method is based on the work of Gutenberg and Richter in which the time integral of S -wave ground-motion velocity-squared is measured as a basic metric of the radiated energy. Only stations within a distance of 100 km are used to minimize complex path and attenuation effects. Unlike the teleseismic method that uses mainly P waves, the use of S waves which carry more than 95 per cent of the radiated energy allows us to obtain robust results. We calibrate the method using synthetic seismograms to modernize and improve the Gutenberg–Richter method. We compute synthetic seismograms for a source model of each event with a given source function (i.e. known E R ), the actual mechanism and the source-station geometry. Then, we compare the given E R with the computed energy metric to correct for the unknown effect of wave propagation and the mechanism. The use of downhole records minimizes the uncertainty resulting from the site response. Our results suggest that the currently available estimates of E R from teleseismic data are probably within a factor of 3, on average, of the absolute value. The scaled energy e R ( = E R / M 0 ) is nearly constant at about 3 × 10 −5 over a magnitude range from M w  = 5.6 to 7.0 with a slight increasing trend with M w . We found no significant difference in e R between dip-slip and strike-slip events.